A novel technique for the solution of second-order difference equations. - Senior, T.B.A (IEEE Transactions on antennas and propagation)
The class of second-order difference equations that arise in the diffraction of a plane wave at skew incidence on an impedance wedge is investigated. For a typical equation which was solved by the introduction of elliptic integrals, it is shown that the solution can be obtained in a very trivial manner from a convolution-type integral equation and the results are in complete agreement with those previously found